Penapisan Kadar Kolesterol Total dan HDL sebagai Upaya Pencegahan Gangguan Lipid dan Penyakit Kardiovaskular di Kelurahan Tanjung Duren Selatan - Frisca Frisca; Santoso, Alexander Halim; Destra, Edwin; Pranata, Catherine Christiana; Ramadhani, Kenzie Rafif; Alwini, Muhammad Rifat Umar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Imbalance of body lipid levels, especially total cholesterol and HDL, is a major risk factor for cardiovascular disorders. A simple lipid profile examination can be used to detect potential atherogenic dyslipidemia that has not shown clinical symptoms. Total cholesterol and HDL levels were examined in 104 participants using the Point-of-Care Testing (POCT) technique. Education was provided individually using leaflets, which contained information on the effects of saturated fat and trans fat consumption, and the importance of unsaturated fat and fiber intake on lipid profiles. Most participants had total cholesterol levels within normal limits. However, more than half of the population showed low to very low HDL levels, indicating hidden metabolic risks. Dietary education was provided in a targeted manner according to the results of each participant's examination. Total cholesterol and HDL examinations were used to assess the risk of lipid disorders early on. Nutrition education based on examination results is useful in raising awareness of the importance of regulating diet to reduce the risk of atherosclerosis and cardiovascular complications.